2021
DOI: 10.3390/languages6040182
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pronunciation Awareness Continuum through Self-Reflection in the L2 French Learning Process

Abstract: Second language (L2) researchers have established that examining learners’ awareness of their own learning process and progress is essential. However, learners exposed to the same input in the classroom may differ in the way that they perform. This difference may be due to the way and depth with which learners process the L2 information. The present study explores self-reflection (i.e., introspective verbal reports) to enhance L2 learning, helping learners develop an awareness of learning as a process. This fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Multiple studies have concluded that self-reflection is an indispensable element in the language learning process. Meritan's (2021) research indicates that self-reflection has been shown to be advantageous in the context of language development, specifically with regard to pronunciation. Furthermore, El-Badri and Abu-baker (2021) provided evidence that the most efficacious approach to enhancing one's understanding of English text is through the practice of self-reflection.…”
Section: Metacognition and Self-reflection In Language Learningmentioning
confidence: 99%
“…Multiple studies have concluded that self-reflection is an indispensable element in the language learning process. Meritan's (2021) research indicates that self-reflection has been shown to be advantageous in the context of language development, specifically with regard to pronunciation. Furthermore, El-Badri and Abu-baker (2021) provided evidence that the most efficacious approach to enhancing one's understanding of English text is through the practice of self-reflection.…”
Section: Metacognition and Self-reflection In Language Learningmentioning
confidence: 99%